2004
DOI: 10.1002/jmv.20129
|View full text |Cite
|
Sign up to set email alerts
|

Epstein‐barr virus (EBV) in healthy carriers: Distribution of genotypes and 30 bp deletion in latent membrane protein‐1 (LMP‐1) oncogene

Abstract: There are two types of Epstein Barr virus (EBV): EBV-1 and EBV-2, distinguished by genomic polymorphism in the genes encoding the nuclear antigens (EBNA-2, -3A, -3B, -3C). Latent membrane protein 1 (LMP-1) is an EBV protein with known oncogenic properties. Different variants had been described; among them, a 30 base pair (bp) deletion (del-LMP-1) had been reported in benign and malignant pathologies, but there is little information about its frequency in healthy populations. The aim of this study was to determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
32
4
3

Year Published

2006
2006
2012
2012

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 30 publications
10
32
4
3
Order By: Relevance
“…These results confirmed previous observations in which an association between del30 and high rep33 numbers and between del30 and ins15 had been documented in HL samples from Argentina and Brazil (14). In contrast, in our region a very low incidence of del30 variants and a low number of rep33 copies was previously described among healthy individuals (4,8). To the best of our knowledge, the 15-bp insertion encoding a JAK3 signaling motif has been described only within the third repeat of rep33 in B95.8-related sequences (14,28,40).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…These results confirmed previous observations in which an association between del30 and high rep33 numbers and between del30 and ins15 had been documented in HL samples from Argentina and Brazil (14). In contrast, in our region a very low incidence of del30 variants and a low number of rep33 copies was previously described among healthy individuals (4,8). To the best of our knowledge, the 15-bp insertion encoding a JAK3 signaling motif has been described only within the third repeat of rep33 in B95.8-related sequences (14,28,40).…”
Section: Discussionsupporting
confidence: 93%
“…adults with IM were infected with multiple LMP1 variants, and their distribution fluctuated dynamically between OS and PBMC over time (8,27,35,36); however, no coinfections with LMP1 variants were observed in the pediatric patients with IM studied here. On the other hand, coinfection with two EBV variants was detected in a low proportion (3/15) of IM patients in different compartments at some time point during the study when other EBV genes were assessed (Table 3) (24,25).…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Most of the pediatric IM cases described here, 9/10, were infected with EBV1 and only 1 patient presented with EBV2 infection. This is in accordance with Correa et al [2004], who described that 75.9% of adult healthy carriers from Argentina were infected with EBV1. Interestingly, no pediatric patient evidenced co-infection with both EBV1 and EBV2, in contrast to the 6.5% co-infection described in adult healthy carriers by Correa et al [2004].…”
Section: Resultssupporting
confidence: 93%
“…Moreover, the 30 bp deletion of the LMP-1 gene, which has been associated with a higher oncogenic potential (Knecht et al, 1993), was revealed only in EBV DNA from a normal adrenal gland. This distribution of EBV genotypes and 30 bp Polyomaviruses and herpesviruses in human adrenal tumors L Barzon et al deleted LMP-1 variant is similar to the prevalence observed in blood samples from EBV healthy carriers attending our Clinical Microbiology Laboratory in Padova (unpublished observations) and to the prevalence reported in other institutions (Gratama and Ernberg, 1995;Correa et al, 2004). To assess whether EBV infection in adrenal tissues was latent or lytic, we analysed expression of transcripts of EBV latent genes (EBER, EBNA-1, EBNA-2, EBNA-3C, LMP-1 and LMP-2) by reverse transcription (RT)-PCR, as reported (Isobe et al, 2004), and expression of EBNA-1 protein and EBV early antigen-diffuse (EA-D), which is expressed during lytic activation, by immunohistochemistry.…”
supporting
confidence: 83%